Comparative Genomic Analysis of Two Vibrio toranzoniae Strains with Different Virulence Capacity Reveals Clues on Its Pathogenicity for Fish - Lasa, Aide; Gibas, Cynthia J.; Romalde, Jesús L. (Frontiers in Microbiology, 2017)
Vibrio toranzoniae is a Gram-negative bacterium of the Splendidus clade within the Vibrio genus. Vibrio toranzoniae was first isolated from healthy clams in Galicia (Spain) but recently was also identified associated to disease outbreaks of red conger eel in Chile. Experimental challenges showed that the Chilean isolates were able to produce fish mortalities but not the strains isolated from clams. The aim of the present study was to determine the differences at the genomic level between the type strain of the species (CECT 7225T) and the strain R17, isolated from red conger eel in Chile, which could explain their different virulent capacity. The genome-based comparison showed high homology between both strains but differences were observed in certain gene clusters that include some virulence factors. Among these, we found that iron acquisition systems and capsule synthesis genes were the main differential features between both genomes that could explain the differences in the pathogenicity of the strains. Besides, the studied genomes presented genomic islands and toxins, and the R17 strain presented CRISPR sequences that are absent on the type strain. Taken together, this analysis provided important insights into virulence factors of V. toranzoniae that will lead to a better understanding of the pathogenic process.